2021
DOI: 10.1097/aud.0000000000001038
|View full text |Cite
|
Sign up to set email alerts
|

Audiologic Profiles of Children With Otitis Media With Effusion

Abstract: Objectives: To describe the impact of effusion volume, viscosity, and purulence on the audiologic profiles of children with otitis media with effusion. Design: Fifty-one ears from children between the ages of 8 months and 11 years who had a diagnosis of otitis media with effusion and were scheduled for tympanostomy tube placement were recruited from medical clinics. The control group consisted of 17 ears from children between the ages of 10 months and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 51 publications
4
16
0
Order By: Relevance
“…However, as described above, the commonly used physiologic test to detect OME (tympanometry) only has an overall accuracy of 84% and is not sensitive to small changes in middle ear mechanics. This is consistent with what was observed by Al-Salim et al 2021, as there was no systematic effect of effusion volume on outcomes for standard 226 Hz tympanometry. Thus, there exists a need for a diagnostic measure that can provide information on effusion characteristics, specifically effusion volume.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, as described above, the commonly used physiologic test to detect OME (tympanometry) only has an overall accuracy of 84% and is not sensitive to small changes in middle ear mechanics. This is consistent with what was observed by Al-Salim et al 2021, as there was no systematic effect of effusion volume on outcomes for standard 226 Hz tympanometry. Thus, there exists a need for a diagnostic measure that can provide information on effusion characteristics, specifically effusion volume.…”
Section: Introductionsupporting
confidence: 91%
“…Recent work from our laboratory demonstrated that the volume of an effusion present in the middle ear space directly impacts how much hearing loss occurs as a result of a given episode of OME (Al-Salim et al, 2021). Children that had ears with full effusions, or middle ear effusions that filled the entire middle ear cavity, generally had a flat moderate CHL with a mean 4 frequency pure-tone average of 43 dB HL in those ears.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike that with OAEs, the validity of ABR results is not affected by the presence of OME, beyond the impact of any conductive hearing loss that the OME may be causing. 105 Although some have advocated for performing ABR testing under general anesthesia concurrent with tympanostomy tube insertion, some children with OME have worse ABR thresholds following tube insertion, and results must be interpreted with caution. 106,107 Further discussion of ABR in hearing assessment related to tympanostomy tubes is beyond the scope of this guideline and should be based on shared decisions with the clinician, family, and audiologist.…”
Section: Guideline Key Action Statementsmentioning
confidence: 99%
“…Auditory brainstem response (ABR) testing is another physiologic measure of hearing that might be useful when behavioral audiometry is not feasible. Unlike that with OAEs, the validity of ABR results is not affected by the presence of OME, beyond the impact of any conductive hearing loss that the OME may be causing 105 . Although some have advocated for performing ABR testing under general anesthesia concurrent with tympanostomy tube insertion, some children with OME have worse ABR thresholds following tube insertion, and results must be interpreted with caution 106 , 107 .…”
Section: Guideline Key Action Statementsmentioning
confidence: 99%
“…Moreover, 226-Hz tympanometry has a poor correlation to the severity of the conductive hearing loss in OM. 42 Additionally, Al-Salim et al 43 have shown that effusion volume, which was determined surgically, was correlated with outcomes from several audiological tests, including the degree of the conductive hearing loss as determined by ABGs, the presence of the otoacoustic emission, and ABR wave V latency, but noted no correlation with 226-Hz tympanometry. For the detection and determination of MEE volume, and the type of effusion in the middle ears of children, the American Academy of Otolaryngology has recommended the use of pneumatic otoscopy.…”
Section: Otitis Media and Middle Ear Effusionmentioning
confidence: 99%